Kepemimpinan Kepala Sekolah Kunci Keberhasilan dalam Pencapaian Kualitas Pendidikan - Ahmad Mukhlasin (Alignment:Journal of Administration and Educational Management, 2021)
The purpose of this study is to understand the principal's leadership as the key to success in achieving quality education. This research method is library research. The results of the study show that all efforts in improving the quality of education that are carried out cannot be separated from the role of the principal as a leader in the school. In addition, as a school principal, he must involve all education stakeholders in an effort to improve the quality of education. The principal is needed for at least four reasons, namely because many people need a leader figure, in some situations a leader needs to appear to represent his group, as a place to take risks in the event of pressure on his group, and as a place to put power. In conclusion, the right role of the principal can improve the quality of education. With good quality education, it will produce better quality human resources, and will be able to bring this nation to compete in a healthy manner in all fields in the international world. Keywords: Principal, Leadership, Quality of Education